2012
DOI: 10.4236/ape.2012.23022
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Voice Online: Experiences of PE in Finnish Schools

Abstract: The aim of this descriptive study was to find out how people describe their experiences of physical education (PE) in Internet discussion forums. The data for this study were collected during one randomly chosen week in April 2007 via a Google™ search using the Finnish word "koululiikunta" [school PE]. The first 200 hits lead into nine discussion forums, which were analysed by using qualitative content analysis. These nine discussion forums included all together 356 messages. For searching these discussion for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…To ensure reliability, the data were coded twice and in case of unclear or ambiguous messages our research team classified them as a team in order to avoid subjectivity. A detailed description of the categorization process is given in Lauritsalo, Sääkslahti, and Rasku-Puttonen (2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure reliability, the data were coded twice and in case of unclear or ambiguous messages our research team classified them as a team in order to avoid subjectivity. A detailed description of the categorization process is given in Lauritsalo, Sääkslahti, and Rasku-Puttonen (2012).…”
Section: Discussionmentioning
confidence: 99%
“…In her alienation -non-alienation model, extrinsic factors (teacher personality and behaviour, curriculum, class environment and out-of-school influences) as well as intrinsic factors (ability, self-esteem and student beliefs) combined to yield the meaning the classes have for students . Earlier research that listened to the voices of the writers in Internet discussion forums relating to PE (Lauritsalo, Sääkslahti, and Rasku-Puttonen 2012) showed that negative experiences were more common in that environment than positive ones. We argue that it is important to know more about the extrinsic and intrinsic factors that underlie these experiences and learn from them for the benefit of future teacher education.…”
Section: Introductionmentioning
confidence: 99%
“…PE programs around the world are under strong pressure to demonstrate that their practices are effective in preparing students for successful healthy active lifelong living (Lauritsalo, Saakslahti, & Rasku-Puttonen, 2012). Hungary is no exception.…”
Section: Discussionmentioning
confidence: 99%
“…Political and societal pressures are placing PE programs under strong pressure to demonstrate that their practices are effective in promoting learning and preparing students for successful healthy active lifelong living (Lauritsalo, Saakslahti, & Rasku-Puttonen, 2012). Ha et al (2004) highlighted that certain curricular changes are aimed at transforming PE from a skill-oriented curriculum to a more comprehensive educational-developmental and health-related curriculum.…”
Section: Challenges and Development In Pe Curriculummentioning
confidence: 99%
“…Research conducted by Lauritsalo, Sääkslahti, & Rasku-Puttonen (2012), however, outlined some factors that determined both positive and negative attitudes toward PE. This is nothing new.…”
Section: Introductionmentioning
confidence: 99%